2012
DOI: 10.1038/ni.2388
|View full text |Cite|
|
Sign up to set email alerts
|

TGF-β is responsible for NK cell immaturity during ontogeny and increased susceptibility to infection during mouse infancy

Abstract: A major gap in our understanding of infant immunity is why natural killer (NK) cellresponses are deficient, making infants more prone to viral infection. Here we demonstrate that transforming growth factor-β (TGF-β) was responsible for NK cell immaturity during infancy. Higher numbers of fully mature NK cells were found in CD11cdnR mice, whose NK cells lack TGF-βR signaling. Importantly, ontogenic maturation of NK cells progressed faster in the absence of TGF-β signaling, resulting in the formation of mature N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
3
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 46 publications
8
113
3
4
Order By: Relevance
“…In neonates, blocking TGF-b signaling on NK cells promotes faster NK maturation and reduces susceptibility of neonates to viral infection (Marcoe et al 2012). In adults, TGF-b inhibits IFN-g and T-bet expression in NK cells, thus inhibiting type 1 immunity (Laouar et al 2005;Yu et al 2006).…”
Section: Nk Cellsmentioning
confidence: 99%
“…In neonates, blocking TGF-b signaling on NK cells promotes faster NK maturation and reduces susceptibility of neonates to viral infection (Marcoe et al 2012). In adults, TGF-b inhibits IFN-g and T-bet expression in NK cells, thus inhibiting type 1 immunity (Laouar et al 2005;Yu et al 2006).…”
Section: Nk Cellsmentioning
confidence: 99%
“…Moreover, TGF-b is constitutively present in the CSF and was found to modulate macrophages (82). Because TGF-b was recently shown to negatively regulate maturation of NK cells, it might be relevant to investigate ex vivo whether particular CSF constituents might modify NK cell phenotypes (83). The reason for the presence of immature NK cells in the healthy CNS needs further experiments to delineate whether the brain influx of NK cells is dependent on their phenotype or whether it is the CNS milieu that further influences such influx.…”
Section: Nk Cell Modifications Associated With Cns Disordersmentioning
confidence: 99%
“…What about NK cell differentiation? A recent article from Marcoe et al 66 demonstrated that TGF-b limits NK cell numbers in mice by controlling NK cell maturation. In fact, in the absence of TGF-b, ontogenic maturation from HSC to NK cells was faster.…”
Section: Interaction Between Nk Cells and Treg Cells In Hematopoieticmentioning
confidence: 99%